Lifescripts, 3rd Edition - Pollan, Stephen; Levine, Mark, 1958- (Wiley, 2019)
Expertly navigate any workplace conversation and come out on top When confronted with difficult situations in the workplace, many people are at a loss for words. That's why New York Times bestselling authors Stephen M. Pollan and Mark Levine created Lifescripts: What to Say to Get What You Want in Life's Toughest Situations . Using two-color flowcharts, Lifescripts maps out 171 difficult conversations, guiding you through discussion openers and effective responses reach the desired result. This completely revised and updated edition includes nearly 50 new business-focused scripts covering everything from apologizing for a misdirected email to requesting better meeting manners. Inside, you'll find scripts to fit any situation you're confronting at work. Use the signature Lifescripts visual flowcharts to work your way through exactly how the conversation should go. Be it boosting employee morale or getting the raise you deserve, when the time comes, you'll be prepared not only with the right words and phrases, but with the confidence you need to get what you want. Work your way through conversation scripts for terminations, performance reviews, negotiating job offers, asking for raises, and much more Learn a unique set of icebreakers, pitches, questions, answers, and defenses for each difficult conversation Easily develop a winning conversational strategy using the signature visual flowcharts unique to Lifescripts Get strategic tips on attitude, timing, preparation, and behavior to help make any conversation a success This revised Third Edition of Lifescripts is here to help employees and managers communicate even more clearly and effectively. Whatever the situation, Lifescripts provides a road map to navigate the most perplexing, problematic dialogues for success.